Carbon Dioxide Removal with Tuff: Experimental Measurement of Adsorption Properties and Breakthrough Modeling Using CFD Approach. (November 2016) - Aquino, Andrea; Bonamente, Emanuele; Buratti, Cinzia; Cotana, Franco; Castellani, Beatrice; Paolini, Valerio; Petracchini, Francesco
Abstract: This work presents the study of tuff as an alternative material for CO2 capturing and removal by pressure swing adsorption techniques. Tuff represents an economic and environmentally sustainable alternative to commonly-used synthetic zeolites. The proposed methodology includes a laboratory characterization of the CO2 adsorption process under different operative conditions and experimental layouts. Measured data are also used to setup computational fluid dynamics simulations of the fixed-bed adsorption column. Results can be used to define optimal design parameters needed to implement and to improve different applications for biogas upgrading (CO2 /CH4 ratio adjustment) or carbon capture and storage.